Digital Marketing for Cultural Tourism Development: A Case Study of the Cireundeu Indigenous Village, Cimahi City, Indonesia - Nunung Sanusi; Muchsin Al-Fikri; Adi Permana Sidik (International Journal of Nusantara Islam, 2026)
The rapid advancement of information technology has positively influenced various aspects of society, including the indigenous community of Cireundeu Village in Cimahi City, West Java. The community has adopted digital marketing, particularly through Instagram, as part of the transformation of the indigenous village into a cultural tourism destination and an active participant in regional tourism development. This study focuses on community-based tourism in the Cireundeu Indigenous Village, emphasizing the role of digital marketing in developing cultural tourism while fostering an open and sustainable tourism ecosystem. The objectives of this study are threefold: (1) to examine the role of Instagram as a digital marketing platform in the development of cultural tourism in the Cireundeu Indigenous Village; (2) to identify the commodification of cultural tourism that has the potential to increase the community's economic income; and (3) to analyze the management of digital marketing practices implemented within the village. This research employs a qualitative case study approach, with data collected through in-depth interviews, field observations, and documentation studies. The findings indicate that Instagram-based digital marketing has significantly contributed to the development of cultural tourism in the Cireundeu Indigenous Village and has positively impacted the economic growth of the surrounding community. However, the management of digital marketing activities has not yet reached its optimal level. Therefore, the community should strengthen its digital marketing strategies by expanding its promotional activities beyond Instagram to other social media platforms, particularly TikTok. Furthermore, greater involvement of visitors in sharing their travel experiences is essential to broaden promotional reach and attract more diverse tourist segments.